The Critical Discourse Analysis of Translation Shift in إسرائيل /Israel/ in Republika - Nur Aisiyah Fadhilah; Apipudin Apipudin (Proceedings of AICS - Social Sciences, 2018)
This research studies the translation shift in the word ‘Israel’. Word ‘Israel’ initially referred to the Prophet Ya’qub, but in the present, the meaning has shifted to the state of Israel in the association with colonizer and Zionist. This study aims to analyze chronological history of the shifting meaning of the word Israel and the discourse that was built in it. This research uses qualitative method with descriptive approach. The data contained in this research is sourced from mass media of Republika online was entitled "The Israeli Plane Attacked Syria" which was published on Tuesday, 9 December 2014. This study uses the approach of Critical Discourse Analysis model of Norman Fairclough (1995) and translation shift theory of Abdul Chaer (2014). Based on the headline, the authors successfully found 20 propositions. From the findings, the meaning of the word Israel in the news published by Republika online has undergone a shift in the overall field of meaning because Israel described in the online newspaper Republika no longer means a prophet Ya’qub with his prophetic properties, but Israel those who have war equipment and their actions are always trying to intimidate and occupy other countries around it.Keywords:critical discourse analysis, Israel, translation shift, newspaper.